2014
DOI: 10.1590/1414-431x20143895
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal management, pregnancy and pediatric outcomes in fetuses with septated cystic hygroma

Abstract: It has been reported that, compared with simple increased nuchal translucency, fetal cases with septated cystic hygroma (CH) are more likely to face perinatal handicaps. However, pediatric outcomes and proper prenatal counseling for this anomaly have not yet been truly defined. We performed this study to determine pregnancy and pediatric outcomes of fetuses with septated CH. We searched records for cases with septated CH and collected data for structural abnormalities, karyotype analysis, and pregnancy outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
15
2
Order By: Relevance
“…We think our findings may be helpful to physicians providing parental counseling for women who refuse karyotype analysis. In fetuses with cystic hygroma with normal karyotype and in whom no structural malformations are present, pregnancy outcomes may be favorable as reported in the literature (5).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We think our findings may be helpful to physicians providing parental counseling for women who refuse karyotype analysis. In fetuses with cystic hygroma with normal karyotype and in whom no structural malformations are present, pregnancy outcomes may be favorable as reported in the literature (5).…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Sanhal et al (5) reported that 90% of fetuses (euploid Other than fetal karyotyping, chromosomal microarray analysis (CMA) is an advanced technology with the ability to survey the entire genome and to identify chromosomal abnormalities, submicroscopic genomic alterations. Increased nuchal translucency and cystic hygroma are associated with different conditions, aneuploidy and structural abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] Turner syndrome and Down syndrome have been found to be the most common karyotype abnormalities in different case series in CH cases. [13,14] In this large-scale case study, aneuploidy was detected in 54% of 729 cases and major congenital anomaly was observed in 28% of patients with normal karyotypes. [15] In literature, two important parameters, CH septation and nuchal translucency, are mentioned and if they affect the rate of karyotype anomalies and fetal outcomes in CH patients.…”
mentioning
confidence: 80%
“…The first one is whether or not CH is septation and the second one is nuchal thickness. [14,15] In this study; we retrospectively analyzed our patients who were referred to our clinic with CH at the first or second trimester of pregnancy and whose CH was detected and karyotype analysis was performed. We evaluated these fetuses separately in terms of NT and septation.…”
mentioning
confidence: 99%